Letter - Bowman, E.
035-0102-001 Stretford Trades Council. Hon. Secretary: E. BOWMAN. HALLOWDENE. OAKFIELD, ASHTON-ON-MERSEY. 24/11/42 Sir Walter Citrine Dear Sir In reply to your letter of Oct 15th, I have to inform you my Council support the T.U.C. memorandum on Education after the War. Could you please send us one dozen copies at 6d each. PC 26/11 Despatched Yours faithfully E. Bowman Hon Sec EAB P.S. At our monthly meeting on Nov 19th, it was resolved we ask the T.U.C. to do everything possible for members of the International Brigade in occupied & unoccupied Europe, & North Africa. EB EAB 292/946/35/102